Hayalet çizgi - Akay, Ali; Calikoglu, Levent (Istanbul : Akbank Kültür Sanat Merkezi, 2004)
Birsel, Selim ; Celebi, Elif ; Erdogmus, Tayfun ; Erkmen, Ayse ; Eviner, Inci ; Gediz, Leyla ; Ogut, Ahmet ; Ozkaya, Serkan ; Ozmen, Sener ; Paker, Seza ; Suvari, Gokce ; Taktak, Yusuf ; Tulin, Fatma
boek
Keywords: Turkije